2006
DOI: 10.1074/jbc.m602014200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycins Trigger a Novel Ron Degradative Pathway, Hampering Oncogenic Signaling

Abstract: Ron, the tyrosine kinase receptor for macrophage-stimulating protein is responsible for proliferation and migration of cells from different tissues. Ron can acquire oncogenic potential by single point mutations in the kinase domain, and dysregulated Ron signaling has been involved in the development of different human cancers. We have previously shown that ligand-activated Ron recruits the negative regulator c-Cbl, which mediates its ubiquitylation and degradation. Here we report that Ron is ubiquitylated also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 51 publications
1
33
1
Order By: Relevance
“…Therefore, Hsp90 inhibitors, by causing inactivation, destabilization, and eventual degradation of the client proteins, exhibit potent antitumor activity (46). Growing evidences showed that such effects are mostly mediated by chaperone-dependent ubiquitin ligase CHIP, which is independent of Cbl ubiquitin ligase and does not require the kinase activity of oncoproteins (32,35,(47)(48)(49). More importantly, nascent kinases and some mutant forms of RTKs, which either escape from Cbl-negative regulation or resist to their inhibitors, still remain sensitive to CHIP overexpressionor geldanamycin/17-AAG-induced degradation (32,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Hsp90 inhibitors, by causing inactivation, destabilization, and eventual degradation of the client proteins, exhibit potent antitumor activity (46). Growing evidences showed that such effects are mostly mediated by chaperone-dependent ubiquitin ligase CHIP, which is independent of Cbl ubiquitin ligase and does not require the kinase activity of oncoproteins (32,35,(47)(48)(49). More importantly, nascent kinases and some mutant forms of RTKs, which either escape from Cbl-negative regulation or resist to their inhibitors, still remain sensitive to CHIP overexpressionor geldanamycin/17-AAG-induced degradation (32,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…These studies imply that Smads act as transcriptional repressors of RON, perhaps in a manner similar to that seen for c-Myc. Studies by others (35) show that RON protein turnover is mediated through ubiquitylation/proteasome pathway. Our studies indicate that in the absence of exogenous RON ligand RON protein is relatively long lived in both Smad4-intact and Smad4-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that RON protein has a relatively long half-life in both Smad4-intact and Smad4-deficient cells. A recent study (35) showed that degradation of RON protein is through an ubiquitin-proteasome pathway and that heat shock protein 90 (Hsp90), a chaperone protein, stabilizes the RON from proteasome degradation. To examine whether Smad4 might accelerate RON degradation by this mechanism, BxPC3 and Bx/Smad4 cells were treated with an Hsp90 inhibitor, 17-allylamino-17-demethoxy-geldanamycin (17-AAG), and a proteasome inhibitor, MG132.…”
Section: Bmentioning
confidence: 99%
“…This molecule is able to inhibit HGFL-induced phosphorylation of Ron and also has inhibitory effects on the growth of colon cancer cells [54]. Another possible treatment modality for negatively regulating receptor tyrosine kinase activity in human cancers include a class of anti-tumor drugs called geldanamycins, which have recently been shown to inhibit tumor cell growth by preventing proper folding and degradation of oncogenic proteins, including the Ron receptor [55]. These small molecules that negatively modulate Ron activity provide an alternative approach to targeting this receptor in vivo.…”
Section: Targeting Ron As a Therapeutic Approach In Human Cancermentioning
confidence: 99%